Tissue turnover of collagen type I, III and elastin is elevated in the PCLS model of IPF and can be restored back to vehicle levels using a phosphodiesterase inhibitor. Issue 1 (December 2016) - Hansen, Niels; Karsdal, Morten; Brockbank, Sarah; Cruwys, Simon; Rønnow, Sarah; Leeming, Diana
Abstract Background The aim of this study was to develop and validate a model for pulmonary fibrosis, usingex vivo tissue cultures of lungs from bleomycin treated animals, enabling the investigation of fibrosis remodeling using novel biomarkers for the detection of ECM protein fragments. The combination ofin vivo andex vivo models together with ECM remodeling markers may provide a translational tool for screening of potential treatments for IPF. Methods Twenty female Sprague-Dawley rats, twelve weeks of age, were administrated either two doses of bleomycin (BLM) (n = 14) or saline (n = 6) I.T., two days apart. Ten rats were euthanized at day seven and the remaining ten rats at day fourteen, after the last dose. Precision-cut lung slices (PCLS) were made and cultured for 48 h. Ten female Sprague-Dawley rats, twelve weeks of age, were administrated either two doses of BLM (n = 7) or saline (n = 3) I.T., two days apart. The rats were euthanized fourteen days after the last dose. PCLS were made and cultured for 48 h in: medium, medium + 100 μM IBMX (PDE inhibitor), or medium + 10 μM GM6001 (MMP inhibitor). Turnover of type I collagen (P1NP, C1M), type III collagen (iP3NP, C3M) and elastin degradation (ELM7) was measured in the supernatant of the cultured PCLS. Results P1NP, C1M, iP3NP, C3M and ELM7 were significantly increased in supernatants from BLM animals (P ≤ 0.05 –P ≤ 0.0001) when compared to controls. P1NP, C1M, iP3NP, C3M and ELM7 were significantly increased in supernatants from day seven BLM animals compared to day fourteen BLM animals (P ≤ 0.05 –P ≤ 0.0001). P1NP, C1M, iP3NP, C3M and ELM7 were significantly decreased when adding IBMX to the culture medium of fibrotic lung tissue (P ≤ 0.05 –P ≤ 0.0001). C1M, C3M and ELM7 were significantly decreased when adding GM6001 to the culture medium (P ≤ 0.05 –P ≤ 0.0001). Sirius Red and Orcein staining confirmed the presence of collagen and elastin deposition in the lungs of the animals receiving BLM. Conclusions The protein fingerprint technology allows the assessment of ECM remodeling markers in the BLM PCLS model. By combiningin vivo, ex vivo models and the protein fingerprint technology in the fibrotic phase of the model, we believe the chance of translation from animal model to human is markedly increased.